2007
DOI: 10.2190/om.55.4.b
|View full text |Cite
|
Sign up to set email alerts
|

Love of Life and Death Distress: Two Separate Factors

Abstract: The objectives of the current investigation were threefold: a) to explore the gender differences on love of life (a new construct in the well-being domain) and death distress (death anxiety, death depression, and death obsession); b) to explore the relationship between the scales of these constructs; and c) to examine the factorial structure of these scales. The sample was 245 volunteer Kuwaiti college students (53.5% women). Their mean age was 21.9 (SD = 2.3). They responded to the Love of Life Scale, the Dea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
8
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 35 publications
1
8
0
Order By: Relevance
“…The results showed that death obsession was more in girls than boys. The findings were in complete agreement with findings of, Abdel-khalek (2006Abdel-khalek ( , 2007, Abdel-khalek and Lester (2003).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The results showed that death obsession was more in girls than boys. The findings were in complete agreement with findings of, Abdel-khalek (2006Abdel-khalek ( , 2007, Abdel-khalek and Lester (2003).…”
Section: Discussionsupporting
confidence: 90%
“…Abdel-khalek (2007) in connection to the relationship of love to life and death obsession found that women have greater average scores than men in three scales of (death distress, death anxiety and death obsession).…”
Section: Introductionmentioning
confidence: 99%
“…The healthy route is death acceptance. It is important to note that death anxiety does not mean a life has not been well-lived or that the individual does not love life; research has indicated that love of life and death distress are two separate factors that are not necessarily associated (Abdel-Khalek, 2007).…”
mentioning
confidence: 99%
“…Some studies have shown higher death anxiety in women than in men, and in general, there are more sources of death anxiety in women than in men. 33,34 A study by Fortner and Neimeyer showed no significant association between men and women in death anxiety. 35 This is due to the heterogeneous nature of death anxiety across different cultures and in unique individual understanding and behaviors.…”
Section: Discussionmentioning
confidence: 99%